Sociální dovednosti předškolních dětí a jejich vliv na odklad povinné školní docházky a dosahovaný školní úspěch na konci 1. ročníku základní školy - Martin Chvál; Jana Kropáčková (Orbis Scholae, 2018)
The social skills of pre-school age children are one of the most important key areas that are aimed at from the point of view of upbringing and education in kindergartens/nursery schools. The insufficiently developed social skills of a child can create difficulties or even complications for pre-school-age children in the social age group of their peers and, at the same time, can have a truly significant influence on their future entrance to the first grade of primary school. The diagnosis of social skills is not a simple matter; it will always depend on the person responsible for performing it and how well the person knows the specific child, keeping in mind the child’s behaviour in a certain spectrum of situations − the child may react to one person in a very different way than to another one. Nevertheless, in the CLoSE Project an evaluation guide has been created and established and with its help selected pre-school teachers have evaluated more than 800 children out of a representative kindergarten sample in the Czech Republic. The evaluation guide consisted of eight specific scales and a general summarizing one that were related to readiness to commence school attendance. The scale contained five grades with a detailed description of the maximum scale grades. All the items and batteries taken together showed good psychometric qualities (internal consistency of 0.872) and served as suitable variables at the beginning of the longitudinal observation of the children, who were included in the CLoSE Project during the transitional period between their attendance of kindergarten and primary school. The aim of the research study presented here is to look closely at, use, and present the above-mentioned evaluation guide to children’s social skills and selected empirical outcomes, where the power to predict social skills is tested and evaluated compared to pre-mathematical skills and the level of visual perception. It could help parents make a decision about postponing the commencement of compulsory school attendance and predict the success that will be experienced at school at the end of the first grade of primary school as well. The results and outcomes of the research study indicate that a much more important role in the success of children at school is played by an earlier, i.e. previously diagnosed, level of pre-mathematical skills. However, when parents are making the decision about postponing the commencement of school attendance, the social skills of their children still prevail.